Pengaruh Gaya Kepemimpinan terhadap Kinerja Karyawan pada Usaha Kilang Padi Sirime Desa Pidoli Lombang Kecamatan Panyabungan Kabupaten Mandailing Natal - Irna Suriati; Ade Khadijatul Z Hrp; Muhammad Ardiansyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine whether leadership style can influence the progress and decline of employee performance at the Sirime Rice Refinery Business, Pidoli Lombang Village, Panyabungan District, Mandailing Natal Regency. The number of samples used was 30 respondents. The sampling technique in this research uses the Saturated Sampling technique, where all members of the population are used as samples. The data collection techniques used were observation, questionnaires and documentation. The analysis method for this research uses validity tests, reliability tests, normality tests, heteroscedasticity tests, simple linear regression tests, partial tests and coefficient of determination tests. All of these tests were carried out using the SPSS version 25 program. Leadership style has a positive effect on employee performance at the Sirime Rice Refinery Business. Pidoli Lombang Village, Panyabungan District, Mandailing Natal Regency is indicated by a significant t value of 0.000 < 0.05, the R Square value is 0.817, which means that the independent variable or leadership style variable (X) is able to explain the dividend variable or employee performance variable (Y) of 81, 7% while the remaining 18.3% is influenced by other factors. Based on the research results, it can be concluded that leadership style has a positive and significant effect on employee performance with a calculated t value > t table (11,169 > 1.701) on employee performance at the Sirime rice factory, Pidoli Lembang village, Panyabungan sub-district, Mandailing Natal district.